2023
DOI: 10.1002/ldr.4792
|View full text |Cite
|
Sign up to set email alerts
|

Substrate quality overrides soil salinity in mediating microbial respiration in coastal wetlands

Abstract: As productive and essential ecosystems, coastal wetlands have experienced increased environmental impacts such as saltwater intrusion and eutrophication, resulting in significant shifts in microbially mediated ecosystem functions, such as carbon sequestration and nutrient transformations. The soil microbial respiration, a primary process in the transfer of carbon from soil to the atmosphere, is susceptible to environmental changes. However, studies on how salinity affects soil microbial respiration in coastal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…The efficiency of CO 2 fixation pathways is determined by pathway kinetics and energy requirements, which are largely influenced by specific enzymes in the metabolic pathways (Li, Song, et al., 2023). Key enzymes in the rTCA cycle, such as 2‐oxoglutarate synthase (EC1.2.7.3) and isocitrate dehydrogenase (EC1.1.1.42), are known to be highly sensitive to oxygen and are predominantly found in anaerobic and microaerobic environments (Berg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of CO 2 fixation pathways is determined by pathway kinetics and energy requirements, which are largely influenced by specific enzymes in the metabolic pathways (Li, Song, et al., 2023). Key enzymes in the rTCA cycle, such as 2‐oxoglutarate synthase (EC1.2.7.3) and isocitrate dehydrogenase (EC1.1.1.42), are known to be highly sensitive to oxygen and are predominantly found in anaerobic and microaerobic environments (Berg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both in the early and late stages, βG had an important driving effect on soil C fractions and microbial biomass; the two active C fractions, DOC and MBC, were indispensable for modeling; MBC had a large direct positive effect on CO 2 release (p < 0.001), with path coefficients of 0.41 and 0.40, respectively. The important function of MBC has been previously reported [57,58].…”
Section: Possible Pathways Driving Soil C Mineralizationmentioning
confidence: 93%
“…However, the mere fact that the high-salinity treatment would inhibit soil respiration and decrease the mineralization potential phenomenon does not lead to the conclusion that saline soils favor soil C sequestration. It has been shown that the effect of substrate quality on soil respiration is greater than that of salinity in coastal wetlands [57], and that the ratio of fungal-bacterial growth is lower when the soil C quality is higher [18], which improves the microbial C use efficiency. The results of enzyme stoichiometry (Figure 5) also showed that site W was significantly more C-limited than the other two sites under the 32‰ treatment, which is one point of evidence that soil C mineralization was limited by the substrate.…”
Section: Differences In Factors Influencing Soil C Mineralization For...mentioning
confidence: 99%